Temanten.Id Start Up Social Enterprise : Bersatu Kita Mampu Penelitian Terapan Pada Program Wirausaha Merdeka - Chusnul Rofiah; Nuri Purwanto; Langgeng Prayitno Utomo (Develop, 2023)
This article explores Temanten.id start up Apps is a Social Enterprise Business Network focusing on collaborative efforts of young people to strengthen business resilience and sustainability. This approach offers multiple benefits which provide various kinds of conveniences for holding special Javanese weddings including counting auspicious days, as well as various complete wedding preparation ceremony https://bit.ly/E-Katalog_TEMANTEN with high-quality services at affordable prices and provide students with an authentic work experience to be flexible, operate on a project basis, and prepare themselves for a 'portfolio career'. future. The case study approach builds on previous studies (Adler & Clark, 1991; Leonard-Barton, 1992; Von Hippel & Tire, 1995; and Hoopes & Postrel, 1999). Case studies on 216 new businesses founded by 610 students from 60 universities throughout Indonesia to become new entrepreneurs. Investigating entrepreneurial product development and product development performance under multiple knowledge auspices, the authors conducted multidivisional comparative case studies, testing new products through product validation programs conducted during the learning process. Findings/Results: Temanten.Id Start Up Social Enterprise in Collaborative Business Development Run by Students: Opportunities for Students and SMEs: (1) Structure; (2) Revenue Sharing; (3) Opportunity; (4) Partner Selection and Commercialization; (5) Recruiting Operational Challenges; (6) Conceptual Future Expansion/Expansion Model; (7) Mission, Students can be better prepared for careers to gain valuable work experience before graduating as PWM participants through this model. During the PWM process, the Temanten.id team learned important points to avoid failure in startup development, including: (1) Product Time; (2) Product design; (3) Improper Distribution or Sales Strategy; (4) Unclear Business Definition; (5) Excessive reliance on a single customer; (6) Initial Capitalization; (7) Assume Debt Instruments; (8) Problems with Venture Capital (9) Ineffective team; (10) Personal problems; (11) One Track Thinking; (12) Cultural/Social Factors.